Analisis perbandingan kinerja keuangan perusahaan sebelum dan sesudah akuisisi pada perusahaan pengakuisisi yang terdaftar di bei tahun 2010-2021 - Nur Afifah, Liza Anastasia Kinski; Komariah, Siti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Acquisition is a growth strategy to improve company performance by buying shares in other companies. This corporate action has become a trend in Indonesia in 2010. With the hope of becoming more profitable, it turns out that many companies have suffered losses. Several of these companies have proven that the acquisition theory is not necessarily correct, therefore the purpose of this study is to analyze and compare whether there are significant differences in financial performance before and after making acquisitions in 2010-2021. This study uses a quantitative research method with a descriptive approach. The sample in this study were 43 companies. For the analysis technique itself using the Description Test and the Wilcoxon Signed Rank Test. The results of this study are that ROA, CR, and EPS experienced an average increase when the acquisition was made, but this increase did not show a significant difference before or after the acquisition. Then on TATO and DER there was an average decrease when the acquisition was made and this decrease did not indicate a significant difference before or after the acquisition. From the results of the research that has been done, it can be concluded that to see whether the company is experiencing growth or not after the acquisition, it cannot only be seen from the financial performance factor.